"Everyone Deserves a Smartphone?": Understanding the Media's Legitimation of Mobile Technology Use by Syrian Refugees. Issue 6 (2nd November 2019) - Alarcon, Andrea; Baik, Jeeyun; Kim, Do Own (Donna)
Abstract : This study investigates English-speaking media's legitimation of smartphone uses by Syrian refugees to explore how "otherness" is negotiated through technologies. Qualitatively examining the media coverage of the Syrian refugees' use of smartphones between early 2015 and early 2017, we identified rhetorical devices and narrative strategies. The findings indicated a gradual shift in mediated legitimation strategies. In this process, two major themes emerged: (1) strategies to legitimate uses of technology and (2) demystifying refugees. The first theme identified that media articles focused on refugees' instrumental uses of smartphones over the emotional uses as a legitimation strategy, utilizing metaphors and referencing third parties. The second theme showed media coverage further debunked conflation over poverty and precarity while negotiating otherness. Over time, the media coverage started to fall into the "humanitarian imaginary" of refugees by keeping them at the margins as people who need aid, largely limiting their legitimated mobile phone use to pragmatic uses. The findings contribute to understanding how media coverage can shape the way people make sense of the refugee population at a moment in time of technological appropriation amid ongoing political crises.